Expression of coat proteins changes during postnatal development in selected areas of the rat brain - Borgonovo, Janina Edith (2012)
It is well known that clathrin-mediated endocytosis is crucial for the normal functioning and integrity of neurons in the central nervous system. In this study we attempted to correlate the expression of coat proteins with development in different areas of rat brain. By Western blot, we studied the expression of AP-2, GGA1 and GGA2 in striatum, cerebellum, brain stem, cerebral cortex and hippocampus of newborn rats and during post-natal development; 5, 15, 30, 60, 90 or 150 days after birth. We observed that the expression of the α2 subunit of AP-2 increased substantially between the 15th and 30th day after birth in all areas studied, excepting the cerebellum and cortex. On the other hand, the expression of the α1 subunit does not change significantly during the development in any of the areas under study. We also noted that the expression of the μ2 subunit did not follow the pattern of α2 during development. In general terms, the expression of GGA1 and GGA2 followed a similar pattern to that of AP-2, although these proteins increased significantly in the cerebral cortex from the 15th day after birth. Moreover, presenilin-1, a protein associated with aging and neurodegeneration, shows an expression pattern similar to coat proteins in the striatum and cortex. These results suggest that proteins that conform the intracellular transport machinery in the brain cells seems to accompany development, according to the maturation of the different brain areas. © 2012 ISDN.